2009
DOI: 10.1007/s10800-009-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct-hydrothermal synthesis of LiFe1−x Mn x PO4 cathode materials

Abstract: Carbon free LiFe 1-x Mn x PO 4 (x = 0, 0.05, 0.1, 0.2, 0.4) cathode materials were prepared by a directhydrothermal process at 170°C for 10 h. The structural and electrochemical properties of the samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), charge-discharge experiments, cyclic voltammetry (CV) and alternating current (AC) impedance spectroscopy. The electrochemical performance of LiFe-PO 4 prepared in this manner showed to be positively affected by Mn 2? -substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Chen & Whittingham (2006) showed that the concentration of the antisite defects could be minimized by going to higher synthesis temperatures, i.e. above 443 K. Several other groups have further developed this synthesis approach (Meligrana et al, 2006;Liang et al, 2008;Kuwahara et al, 2008;Jin & Gu, 2008;Dokko et al, 2006;Tajimi et al, 2004;Liu et al, 2009;Ellis et al, 2007), and manganese-substituted compounds have also been synthesized using hydrothermal methods (Xu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Chen & Whittingham (2006) showed that the concentration of the antisite defects could be minimized by going to higher synthesis temperatures, i.e. above 443 K. Several other groups have further developed this synthesis approach (Meligrana et al, 2006;Liang et al, 2008;Kuwahara et al, 2008;Jin & Gu, 2008;Dokko et al, 2006;Tajimi et al, 2004;Liu et al, 2009;Ellis et al, 2007), and manganese-substituted compounds have also been synthesized using hydrothermal methods (Xu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The same material obtained by Yoncheva et al [36] at 500 °C starting from a phosphonate-formate precursor, freeze-drying an aqueous solution containing Li, Fe and Mn phosphate and formate ions, on the other hand, showed a capacity of 140, 120, and 95 mAh/g for x equal to 0, 0.5 and 1, respectively, a C/20. Zhang et al [37] produced LiMn x Fe (1−x) PO 4 /C by solid state reaction with x = 0.7, 0.8, and 0.9, obtaining at C/10 a capacity ranging from 110 to 130 mAh/g as x decreases. Xu et al [38] synthesized carbon free materials through a direct hydrothermal process a 170 °C achieving a capacity of 140, 110, 95, 90, and 78 mAh/g for x equal to 0.1, 0.2, 0.05, 0, and 0.4, respectively, at C/10.…”
Section: Resultsmentioning
confidence: 99%
“…[33] The binding energies of P 2p and O 1s are 133.7 and 531 eV, which indicates the presence of PO 4 3À groups. [34,35] The capacity and cyclability of LiMnPO 4 , Li-Co 0.09 Mn 0.91 PO 4 , and its carbon composites are determined by galvanostatic charge/discharge studies at current rates of 0.05, 0.1, and 0.2 C in the potential limit between 3-4.9 V, as shown in Figure 6 a, b. The initial discharge capacity of the pristine material (70 mAhg À1 ) is smaller than its composite LiMnPO 4 /C, which has a discharge capacity of 140 mAhg À1 at a current rate of 0.1 C. Approximately 85 % of the total capacity obtained in the plateau at 4.1 V corresponds to the redox reaction of Mn 3 + /Mn 2 + coupled with the lithium intercalation/deintercalation into/out of the olivine structure.…”
Section: Resultsmentioning
confidence: 99%